1998
DOI: 10.7589/0090-3558-34.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Condition Indices to Changing Density in a White-Tailed Deer Population

Abstract: I)iseas,. tss(xiati,)mm 199',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
3
26
1
1
Order By: Relevance
“…Many studies have found that cervids in populations suffering from forage competition show a reduced body mass (Leader-Williams and Rickett 1982;Vincent et al 1995;Ashley et al 1998;Sams et al 1998;Hjeljord and Histol 1999). In our study, adult HD-SW male deer reached 87% and 60% of the body mass reached by HD-MW and LD-SW adult deer, respectively, whereas adult HD-SW females reached 74% of the body mass of adult HD-MW females.…”
Section: Size Differences Between Populationscontrasting
confidence: 55%
See 1 more Smart Citation
“…Many studies have found that cervids in populations suffering from forage competition show a reduced body mass (Leader-Williams and Rickett 1982;Vincent et al 1995;Ashley et al 1998;Sams et al 1998;Hjeljord and Histol 1999). In our study, adult HD-SW male deer reached 87% and 60% of the body mass reached by HD-MW and LD-SW adult deer, respectively, whereas adult HD-SW females reached 74% of the body mass of adult HD-MW females.…”
Section: Size Differences Between Populationscontrasting
confidence: 55%
“…Since Cervidae grow during the summer in temperate and cold climates, intensive forage competition during this season should result in a chronic reduction in body size, a phenomenon observed in reindeer and caribou (Rangifer tarandus: Leader-Williams and Rickett 1982; , moose (Alces alces: Sand et al 1996;Hjeljord and Histol 1999), roe deer (Capreolus capreolus: Vincent et al 1995) and white-tailed deer (Odocoileus virginianus: Ashley et al 1998;Sams et al 1998). However, the consequences of forage restriction in summer have not yet been studied under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…No se encontró diferencias por sexo en el caso de la creatinina, lo que concuerda con lo reportado por Sams et al (1998) e ISIS (1999). Sin embargo, se encontraron diferencias (p<0.05) por lugar de procedencia (ZH: 2.5 mg/dl vs PECS: 2.0 y ZCI: 2.1 mg/dl).…”
Section: Resultados Y Discusiónunclassified
“…A/G ratio reflects relative change in albumin and total globulin fractions and is therefore depressed when protein malnutrition and starvation occur. This ratio was also extremely responsive to differing densities in white-tailed deer (Sams et al 1998). It may rise in cases of infection or other disorders when an adequate protein intake occurs (LeResche et al 1974).…”
Section: Discussionmentioning
confidence: 96%
“…These parameters are therefore related to pathological conditions such as parasitic infections. Concentrations of albumin and globulins were found to be the most sensitive physiological indices in white-tailed deer (Odocoileus virginianus) herd density (Sams et al 1998). A/G ratio reflects relative change in albumin and total globulin fractions and is therefore depressed when protein malnutrition and starvation occur.…”
Section: Discussionmentioning
confidence: 99%